Ethnobotanical survey and economic impact of plants used to relieve COVID-19 related infections - Tshepo Aphane; Stanley S. Gololo; Vuyisile S. Thibane (Journal of Medicinal Plants for Economic Development)
Background: In the wake of the global crisis initiated by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak, South Africans explored alternative therapeutic strategies. This exploration was driven by vaccine hesitancy, the emergence of diverse SARS-CoV-2 variants, and the enduring challenges posed by the virus.